A study of the role, contribution and performance of UK board directors - Kakabadse, Andrew P.; Kakabadse, Nada K.; Myers, Andrew (Cranfield University School of Management, 2008)
The quality, integrity, skill and wisdom of UK Board Chairmen is seen to be unimpeachable. However, a comprehensive survey of all FTSE 350 Directors raises question marks over the effectiveness of their contributions to Board performance, effective organisational governance and shareholder accountability. These three concerns offer real opportunities for improved performance.